Hydrogenation of 4-nitrochlorobenzene catalysed by cobalt nanoparticles supported on nitrogen-doped activated carbon. Issue 11 (22nd April 2021) - Villora-Picó, J. J.; Campello-Gómez, I.; Serrano-Ruiz, J. C.; Pastor-Blas, M. M.; Sepúlveda-Escribano, A.; Ramos-Fernández, E. V.
Abstract : The hydrogenation of nitroarenes to produce the corresponding amines using dihydrogen as reducing agent has an important industrial role, since it allows to obtain important added-value products. Abstract : The hydrogenation of nitroarenes to produce the corresponding amines using dihydrogen as reducing agent has an important industrial role, since it allows to obtain important added-value products. This reaction needs the help of a catalyst to proceed. Many catalysts have been already tested and studied. Most of them are based on noble metals supported on metal oxides. These catalysts perform well, but they are expensive and thus, alternative systems are needed. In this context, cobalt-based catalysts have emerged as adequate alternatives, despite cobalt nanoparticles per se are not very active for this reaction. A way to improve the catalytic activity of cobalt nanoparticles is by supporting them on a support with functional groups that are able to change their intrinsic properties and to enhance their catalytic properties. In this sense, N-containing carbons are promising candidates to be used as support, since nitrogen functionalities may modify the catalytic properties of cobalt. In this work, cobalt nanoparticles supported on N-doped activated carbons have been prepared and studied as catalysts for the hydrogenation of 1-chloro-4-nitrobencene to the corresponding chloro-aniline. It is demonstrated that the catalytic activity is enhanced by the presence of nitrogen species in the support. When the temperature of the catalyst activation treatment (reduction under flowing hydrogen) is increased, the catalytic activity increases drastically in the presence of nitrogen functionalities on the support. The catalysts have been characterised by transmission electron microscopy (TEM), temperature-programmed reduction (TPR), X-ray diffraction, X-ray photoelectron spectroscopi (XPS) and N2 adsorption at 77 K. It has been found that the enhanced catalytic activity was due to two different factors, namely the interaction of the cobalt particles with the nitrogen functional groups (forming Co4 N), and the development of mesopores in the support during the activation process that increases the accessibility of reactants to the active sites.